مقاصد الشريعة وإشكالية دوران الأحكام بين التعبد والتعليل: درسة تأصيلية: The Objectives of Sharia (maqasid) and The Problem of The Rulings between Worship and Reasoning: An applied Fundamental Study - Salhab, Belal Barakat Sulaiman (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث يهدف هذا البحث إلى تسليط الضوء على العلاقة بين مقاصد الشريعة والأحكام الشرعية بنوعيها المعللة والتعبدية، ويوضح مدى العلاقة بينها، ويزيل الإشكال المتمثل في عدم وجود دراسة تفسر لنا مدى الارتباط بين مقاصد الشريعة القائمة على فكرة تعليل الأحكام وإدراك حِكمها، وبين الأحكام التعبدية القائمة على التسليم والانقياد لأوامر الله فيها دون النظر إلى عللها وما تحتويه من حكم؛ إذ إنه كيف يمكننا الموازنة بين القول بتعبدية بعض الأحكام والتوقف فيها، وبين ما أقره جماهير العلماء من أن الله عزّ وجل لم يشرع حُكمًا إلاّ لهدف ومقصد، وإلا كان تشريعه لها عبثًا؟ وللإجابة عن هذا الإشكال اتبع الباحث منهجًا وصفيًا يتبين لنا من خلاله المعالم الأساسية لمصطلحات البحث، ومنهجًا تحليليًا تركيبيًا يناقش أقوال العلماء ويسبر أغوارها ويرسم صورة متكاملة توضح مدى العلاقة بين مقاصد الشريعة والأحكام المعللة والتعبدية. ومن خلالها توصل الباحث إلى جملة من النتائج أهمها: أن الحكم التعبدي هو الحكم الذي لا تُدك علته الجزئية القياسية وإن أمكن إدراك الحكمة من تشريعه. أن التعليل هو أساس القول بالمقاصد، وأنه لا يتصور وجود مقاصد للأحكام ما لم تكن تلك الأحكام معللة. إن عدم إدراك العلة الجزئية لأي حكم لا يلزم منه عدم إدراك الحكمة العامة لذلك الحكم، وعليه فلا تعارض بين الأحكام التعبدية التي يمكن إدراك الحكمة منها على رأي الجمهور وبين معرفة مقاصدها. ABSTRACT This paper aims to highlight the connection between the objectives of Sharia law and legal rulings of both reasoning and devotional aspects, it clarifies the extent of the connection between them, and fills the gap opened by lack of adequate study that could explains the extent of the connection between the objectives of Sharia law, which stands on the idea of justifying rulings and understanding the wisdom behind them, and the devotional rulings which are based on total submission to the commands of Almighty Allah without looking at its reasons and the rulings it contains; we need to balance between the worship aspect of some rulings, and what has been the concession of the majority of scholars saying that Allah has not legislated a ruling except for a purpose and objective, otherwise His legislation for it would be in vain? To answer this problem, the researcher followed a descriptive approach through which the basic features of the research terms is explained, and a synthetic analytical approach that discusses the scholars’ views, explores them deeply, and draws a complete picture that clarifies the extent of the relationship between the objectives of Sharia law and the justified and the rulings on worship. The research concludes that: The ruling on worship is the ruling which its partial standard cause cannot be tampered, even if it is possible to understand the wisdom behind its legislation. Reasoning is the basis of the idea of maqasid, and that there could not be objectives for rulings unless those rulings are reasoned. Finally, not understanding the partial reason for any ruling does not necessitate not understanding the general wisdom of that ruling, and therefore there is no conflict between the rulings on worship from which the wisdom could be understood, according to the majority opinion, and knowing their objectives.maqasid.